Transthyretin amyloid cardiomyopathy: Treatment pipeline, clinical trials, and challenges - Sweety Sharma; Bhawna Sharma (Journal of Public Health and Primary Care, 2021)
Transthyretin amyloid cardiomyopathy (ATTR-CM) is potentially a fatal disease characterized by abnormal buildup of amyloid fibrils primarily in the heart causing progressive heart failure. It is categorized into two subtypes-hereditary ATTR and wild type ATTR. Previously, no treatment is available, due to which liver transplantation, multi-organ transplantation, and symptomatic treatment were the only therapies at that time. Approval of Vyndaqel (tafamidis meglumine) and Vyndamax (tafamidis) capsules in 2019, acts like a kick in the research fields due to which other therapeutics are now emerging. Several clinical trials are going on to evaluate the efficacy of different drugs in ATTR-CM. Most of the clinical trials demonstrated positive outcomes which leads to further evaluation for confirmation. In this review treatment pipeline, ongoing clinical trials and challenges related to ATTR-CM are described.